Evaluation of phytochemical content and antioxidant activity in Rubus fraxinifolius fruit extracts using different solvents - Oliver Dean John; Monjia Belleza Cosmas Mojulat; Eunice Lua Hanry; Annals Tatenda Mushunje; Noumie Surugau (e-VIBS, Faculty of Science and Natural Resources, 2025)
Rubus fraxinifolius is one of the wild berries (Rogimot) species native to the highland regions of Southeast Asia, including Sabah, Malaysia. Despite their ethnobotanical significance, studies on its phytochemistry and antioxidant potential remain limited. This study compares the antioxidant activity and phytochemical content of fruit extracts from Rubus fraxinifolius using, 80% methanol, 70% acetone and distilled water. Antioxidant properties were evaluated using DPPH and FRAP assays, while total phenolic content (TPC), total flavonoid content (TFC) and total anthocyanin content (TAC) were also quantified. The results showed that the methanolic extract of R. fraxinifolius had the highest TPC (36.70±0.56 ± 0.44 mg GAE/g), TFC (12.15 ± 0.13 mg QE/g), and TAC (76.41± 71 mg C3G/ 100g) values. Antioxidant analysis showed 80% methanol exhibited the highest DPPH scavenging activity, IC50 = 64.47±5.55 μg/mL, and highest FRAP activity, 71.69±2.88 (μg TE/mL) compared to 70% acetone and distilled water. These findings showed significant variation in phytochemical content and antioxidant activity based on the solvent used, highlighting the importance of solvent selection in optimising bioactive compound extraction. Further research to evaluate its detailed phytocompound components and bioactivity is strongly warranted.